Identificação de Leishmania spp. em amostras de diferentes regiões do tecido cutâneo de cães - Gonçalves, Maria Esther [UNESP] (2004)
The identification of Leishmania spp. in the skin is an important tool for the canine visceral leishmaniasis (CVL) control. The aim of this study was to investigate which would be a better clinically normal skin region to perform skin biopsies for the diagnosis of the naturally Leishmania-infected dogs and to associate this finds to clinical signs. Thirty dogs from an endemic visceral leishmaniasis area and positive diagnose for CVL were selected for the study. Five asymptomatics dogs, negative for Leishmania were included as a fourth group. Clinically normal skin samples were collected from the six different sites by punch biopsy: upper part of the muzzle, ear, thorax, abdomen, forelimb and mucocutaneous junction. Immunohistochemistry detection of Leishmania was performed in all skin biopsy specimens and polymerase chain reaction (PCR) was performed in samples that were Leishmania-negative by immunohistochemistry. Weight loss (95%), lymphadenomegaly (55%) and pale mucous membrane (30%) were the main clinical signs observed. The most frequent skin abnormalities were alopecia and desquamation (90%), ulcerative dermatitis (60%), onychogryphosis (50%) and hyperpigmentation (40%). The immunohistochemistry demonstrated 100% of positivity in all skin samples of symptomatics dogs with skin lesions, independing on the region. Symptomatics dogs without skin lesions showed a lower positivity percentage, 40% and 30% depending on the region and asymptomatics dogs showed 30% and 20%. All regions from group 4 showed negative results. PCR showed positivity rates higher when compared to immunohistochemistry (P< 0,05) for the forelimb region from symptomatics dogs without skin lesions. These findings demonstrated that clinically normal skin of dogs from endemic area have parasites independently of clinical signs.